Growth of trigonal gadolinium fluoride in a glass-ceramic for scintillation and optical applications. Issue 14 (November 2018) - de Faoite, D.; Tobin, I.; Ulyanov, A.; Roberts, O.J.; Shortt, B.; Hanlon, L.; McBreen, S.; Stanton, K.T.
Abstract: This work determines the X-ray powder diffraction peak positions for trigonal GdF3 experimentally and using simulation. An oxyfluoride matrix glass-ceramic containing the inorganic compound GdF3 was synthesised by quench casting followed by controlled heat treatment. X-ray diffraction analysis was used to confirm the amorphous nature of the as-cast glass, and to identify the compounds crystallised in the glass-ceramic by heat treatment. A simulated powder diffraction pattern for trigonal GdF3 was calculated and used to confirm the identity of the compound crystallised in the glass-ceramic as being trigonal GdF3 . Rietveld refinement of the structural model was performed using the measured diffraction pattern to accurately determine the unit cell parameters and asymmetric atomic coordinates. A simulated powder diffraction pattern was then calculated for trigonal GdF3 using the refined structural parameters.